Analisis Sistem Gadai Tanah Pada Perspektif Ekonomi Islam: Study Kasus Desa Sungai Sayang Kecamatan Sadu Kabupaten Tanjung Jabung Timur - Acok Tang; Efni Anita; Nurlia Fusfita (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
There are two issues studied in this thesis, namely (1) How is the Pawn Practice of the Community in Sungai Sayang Village, Sadu Subdistrict, (2) How is the Islamic Economics review of pawning in the Sungai Sayang Village Community, Sadu Subdistrict. The purpose of this study is to find out how the community pawning practice in Sungai Sayang Village, Sadu Subdistrict and to find out how the Islamic economic review of pawning in Sungai Sayang Village community, Sadu Subdistrict. To reveal these problems in depth and comprehensively, the researchers used a qualitative approach by collecting data using observations, interviews, and documentation. The data analysis technique used is field analysis using the interactive model of Miles and Huberman including data reduction, data display, and data verification. From the results of the study, it can be concluded that the practice of community pawning in Sungai Sayang Village, Sadu Subdistrict is that the pawner (rahin) delivers the pledged collateral (marhun) to the pawnee (murtahin) after the pawnbroker receives the money (debt) from the pawn recipient, (rahin) the pawner. The pawn requires that the object being pawned during the period of pawning is the result of the payment of the debt of the pawner to the recipient of the pawn, while the Islamic economic perspective is in the practice of pawning in Sungai Sayang Village, Sadu Subdistrict, namely, in terms of the contract, aqid (the giver and recipient of the pawn), marhun (goods). pawn), marhun bih (debt), there are pawn contracts that are in accordance with Islamic economics, from the aspect of the pillars the conditions are fulfilled, some have not or some are not in accordance with Islamic economics because they contain elements of usury.